Length-weight relationships and condition factors of four dominant fish caught by coral bubu trap on the west coast of Batam Island, Indonesia - Ramses Ramses; Ismarti Ismarti; Fauziah Syamsi (Syiah Kuala University, 2020)
One of the important components in aquatic ecosystems is fish diversity, which is a key factor in determining its functionality. The coral reef fish is one of the aquatic biotas susceptible to pollutants. Besides being able to influence the composition of fish diversity, it also has an impact on its biological factors, such as its length-weight and conditions. This study aims to examine the relationship of length-weight and condition factors of four dominant fishes caught, which are ecologically and economically important, namely Lates calcarifer, Parachaetodon ocellatus, Stephanolepis cirrhifer, and Chelmon rostractus.These fish species were dominantly caught using bubu trap. The results of the length-weight relationship were b3 of all species, with an exponent value of 2.247 for the L. calcarifer; 1.932 for P. ocellatus; 2.74 for S. cirrhifer and 2.84 for C. rostractus. Fulton’s (K) condition factor for L. carifer ranged from 15.55-21.06 (average: 17.95), for P.ocellatus ranging from 27.30-35.59 (average: 30.38), for S. cirrhifer ranged from 17.58-27.23 (average: 21.29), and for C. rostractus ranging from 21.86-30.95 (average: 24.24). While the relative weight (Wr) condition factor average value of L. calcarifer is 102.53, P. ocellatus is 100.88, S. cirrhifer is 101.72, and C. rostractus is 101.11. It is concluded that the fish had an allometrict growth pattern, and condition factor values indicate good aquatic environmental conditions and a balance between prey and predatorKeywords: Length-Weight; Growth Pattern; Condition Factors